Influence of Water Addition on Lipid Oxidation in Protein Oleogels. Issue 9 (31st July 2019) - Meissner, Philipp M.; Keppler, Julia K.; Stöckmann, Heiko; Schrader, Katrin; Schwarz, Karin
Abstract : The aim of the present study is the investigation of lipid oxidation in protein based oleogels. For this purpose, oleogels are prepared by suspension of freeze dried whey protein isolate aggregates and small amounts of water (<10%) in purified oleic rich safflower oil. The formation of conjugated dienes positively correlates with the addition of water. In contrast, a lower concentration of aldehydes is measured by headspace gas chromatography in oleogels with higher water addition, indicating a water facilitated degradation of aldehydes reacting with proteins. Determination of water activity indicates the presence of water droplets at higher water addition to oleogels. Furthermore, changes in the surface appearance (greasy‐glossy to dull) and the texture (consistent gel vs. crumbly) structure are indicative of microstructural changes due to increased water addition. The study suggests that water droplet formation is responsible for the marked increase in lipid oxidation. However, cross reaction of aldehydes with proteins is suggested to result in lowering the levels of secondary lipid oxidation products hexanal and propanal in oleogel. Practical Applications : The practical applications of the present work are related to the fabrication, processing, storage and consumption of oleogels and other protein‐lipid‐matrices. The results clearly indicate oleogels are prone to oxidation and proteins are involved by cross‐reaction resulting in visible browning during storage. Oxidation products such as hexanal (marker for secondary lipid oxidation) may not reflect the level of oxidation due to degradation by cross‐reactions with proteins. The aim of the present study is the investigation of lipid oxidation in protein based oleogels. The formation of conjugated dienes positively correlates with the addition of water. In contrast, a lower concentration of aldehydes is measured in oleogels with higher water addition. Water activity indicates the presence of water droplets at higher water addition to oleogels, which are likely responsible for the marked increase in lipid oxidation. However, cross reaction of aldehydes with proteins is suggested to result in lowering the levels of secondary lipid oxidation products hexanal and propanal in oleogels. Abstract : The aim of the present study is the investigation of lipid oxidation in protein based oleogels. The formation of conjugated dienes positively correlates with the addition of water. In contrast, a lower concentration of aldehydes is measured in oleogels with higher water addition. Water activity indicates the presence of water droplets at higher water addition to oleogels, which are likely responsible for the marked increase in lipid oxidation. However, cross reaction of aldehydes with proteins is suggested to result in lowering the levels of secondary lipid oxidation products hexanal and propanal in oleogels.